KONSEP GAYA BELAJAR SISWA PADA MATA PELAJARAN MULOK KEAGAMAAN - Setyawan, Ari; Shofiyul Himami, Ahmad; Miftahurrahim, Rian (ILJ: Islamic Learning Journal, 2023)
Learning style is the preferred way of processing experience and information. Learning styles are habits that reflect the way we treat the experiences we gain through modalities. The conception of learning styles is an important thing to explore. This study uses the literature research method. The data source is in the form of scientific texts which are analyzed usingcontent analysis. The research results show thatEach student has their own learning style habits. It cannot be forced when students have a visual learning style but are taught with learning strategies that tend to be auditory or kinesthetic learning styles. Learning strategies with learning styles have a close relationship. Likewise in religious grandiose lessons which obviously have different learning styles because there is a lot of practice from theoretical material. Then it is necessary to combine learning styles, including visual learning styles, auditory learning styles, and kinesthetic learning styles